Bevacizumab (BVZ)‐associated toxicities in children with recurrent central nervous system tumors treated with BVZ and irinotecan (CPT‐11): A Pediatric Brain Tumor Consortium Study (PBTC‐022). Issue 23 (19th September 2013) - Fangusaro, Jason; Gururangan, Sridharan; Poussaint, Tina Young; McLendon, Roger E.; Onar‐Thomas, Arzu; Warren, Katherine E.; Wu, Shengjie; Packer, Roger J.; Banerjee, Anu; Gilbertson, Richard J.; Jakacki, Regina; Gajjar, Amar; et al.
Abstract : BACKGROUND: The incidence and spectrum of acute toxicities related to the use of bevacizumab (BVZ)‐containing regimens in children are largely unknown. This report describes the adverse events in a recently completed large phase 2 trial of BVZ plus irinotecan (CPT‐11) in children with recurrent central nervous system tumors. METHODS: Pediatric Brain Tumor Consortium trial‐022 evaluated the efficacy and toxicity of BVZ (10 mg/kg administered intravenously) as a single agent for 2 doses given 2 weeks apart and then combined with CPT‐11 every 2 weeks (1 course = 4 weeks) in children with recurrent central nervous system tumors. Children were treated until they experienced progressive disease, unacceptable toxicity or completed up to a maximum of 2 years of therapy. Toxicities were graded according to the National Cancer Institute Common Terminology Criteria for Adverse Events, version 3.0. Patients who received at least 1 dose of BVZ were included for toxicity assessment. RESULTS: Between October 2006 and June 2010, 92 patients evaluable for toxicity were enrolled and received 687 treatment courses. The most common toxicities attributable to BVZ included grade I‐III hypertension (38% of patients), grade I‐III fatigue (30%), grade I‐II epistaxis (24%), and grade I‐IV proteinuria (22%). Twenty‐two patients (24%) stopped therapy due to toxicity. CONCLUSIONS: The combination of BVZ and CPT‐11 was fairly well‐tolerated, and most severe BVZ‐related toxicities were rare, self‐limiting, and manageable. Cancer 2013 ;119:4180–4187. © 2013 American Cancer Society . Abstract : The combination of bevacizumab and irinotecan (CPT‐11) was fairly well tolerated in children with recurrent central nervous system tumors. Most severe bevacizumab‐related toxicities were rare, self‐limiting, and manageable.